2015
DOI: 10.1371/journal.pone.0128442
|View full text |Cite
|
Sign up to set email alerts
|

APOE-ε4 Allele Altered the Rest-Stimulus Interactions in Healthy Middle-Aged Adults

Abstract: The apolipoprotein E-ε4 allele is a well-known genetic risk factor for late-onset Alzheimer’s disease, which also impacts the cognitive functions and brain network connectivity in healthy middle-aged adults without dementia. Previous studies mainly focused on the effects of apolipoprotein E-ε4 allele on single index using task or resting-state fMRI. However, how these evoked and spontaneous BOLD indices interact with each other remains largely unknown. Therefore, we evaluated the ‘rest-stimulus interaction’ be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…First, we have a relatively small sample size for the MA + FH + APOE4 risk group which may affect the generalizability of the current findings. However, the sample size used in the current study is comparable to previously published work (Xu et al, 2009, Bookheimer et al, 2000, Dennis et al, 2010, Alexander et al, 2012, Yan et al, 2015). Also, we used multivariate PLS analysis of the fMRI data, with permutation and bootstrap to assess the statistical significance of observed results.…”
Section: Discussionsupporting
confidence: 66%
“…First, we have a relatively small sample size for the MA + FH + APOE4 risk group which may affect the generalizability of the current findings. However, the sample size used in the current study is comparable to previously published work (Xu et al, 2009, Bookheimer et al, 2000, Dennis et al, 2010, Alexander et al, 2012, Yan et al, 2015). Also, we used multivariate PLS analysis of the fMRI data, with permutation and bootstrap to assess the statistical significance of observed results.…”
Section: Discussionsupporting
confidence: 66%
“…First, we have relatively small sample sizes for the MA +FH+APOE4 risk groups which may affect the generalizability of the current findings. However, the sample size used in the current study is comparable to previously published work [21,25,50,88,89]. Also, we used multivariate PLS with permutation and bootstrap methods to assess the statistical significance and stability of our fMRI results, which are robust methods that are more amenable for use with smaller sample sizes compared to more traditional univariate fMRI methods [90,91].…”
Section: Discussionmentioning
confidence: 87%
“…Then, although the DMN have been heavily studied and are reported as a promising kind of network to study, current researches have mainly focused on finding some dysfunctional areas with decreased or increased connectivity ( Song et al, 2015 ; Yan et al, 2015 ; Zhu et al, 2018 ; Chiesa et al, 2019 ). There are relatively few studies on global network dynamics of e4 allele group in normal elderly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of resting state functional MRI (rs-fMRI) ( Teipel et al, 2015 ) and APOE studies have reported mixed results ( Cai et al, 2017 ; Luo et al, 2017 ; Caldwell et al, 2019 ; Zhu et al, 2019 ). Some reported decreased functional connectivity ( Yan et al, 2015 ) in APOE e4 allele carriers (APOE4+) compared with non-carries (APOE4-), the others found some increased functional connectivity ( Song et al, 2015 ; Zhu et al, 2018 ), while others didn’t found any differences ( Chiesa et al, 2019 ). At the global whole-brain level, some neurobiologically meaningful graph-theoretic properties have become important indicators for measuring brain functional networks, through which we can understand the altered network architecture in those carrying risk genotype, including a loss of small-world network ( Korthauer et al, 2018 ), a redistribution of hubs ( Wink et al, 2018 ), and a disrupted modular organization ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%